Application Of A Gravity Model To The Bilateral Trade Between Ecuador And Germany - Tonon, Luis; García, Paulo (UDA AKADEM, 2019)
The objective of this research is to determine the influence of the main factors that affect bilateral trade between Ecuador and Germany through the application of a gravity model, seeking to answer the question: how does the bilateral trade flows between Ecuador and Germany affect the size of their economies and the costs of trade? To solve it, an analysis of the bilateral trade flows between Ecuador and Germany in relation to the GDP of each country and the trade costs generated will be carried out. The study covers the period 2002 - 2017 and the information was obtained from official data bases of both countries and the United Nations. For the calculations, the linear regression using least squares was used with the software Microsoft Excel. The findings make it possible to show that Ecuador’s GDP is the most influential factor in bilateral trade flows, while Germany’s GDP has an opposite effect to that expected, decreasing trade when the GDP increases. Likewise, it is determined that, although total trade flows decrease with increasing trade costs, Ecuadorian imports do not decrease in this increase.